Anthroscapes: a robust basis for mapping land quality and sustainable land use patterns - Kapur, Selim; Akça, Erhan; Zucca, Claudio; Berberoglu,Suha; Miavaghi, Somayyeh Razzaghi (Springer, 2019)
The excess exploitation of natural resources dates back to the eighteenth century. Several attempts were made to assess the sustainability of natural resource use by humans. Some management systems defıned as sustainable are quite new when compared to 1000 years old Mediterranean terraces and crop management. The sloping and water defıcient Mediterranean lands forced humans to develop water harvesting techniques and selection of drought-resistant crops. Thus, within the Mediterranean basin, cultivation of drought-resistant carob, olive, fig, and vine on water harvesting terraces became a dominant land management. Following terrace development villages and towns were established around terraces with specialized functions. In the ancient Mediterranean, the settlement centers were not competing with each other but supplementing their distinctive functions as production, processing, and trade centers. This process led to the development of the human-shaped land approach, i.e. the “Anthroscapes”. Korykos, Kızkalesi of today, has set a unique example to the ancient Mediterranean Anthroscapes. The study site revealed a satellite town type development in the area, with still intact water harvesting cisterns, and terrace walls nesting local crops on deep soils transported to the sites by the people or obtained from the karstic soil in-fills by crushing the karst. Such, anthroscapes proved to be a sustainable system not only for the Mediterranean basin but also for the highlands and steppes of Anatolia by sequestrating carbon and water. Modeling and adapting the anthroscape tradition via renovated traditional technologies peculiar to each Anatolian environment will be a reliable guide for mitigating the current and future environmental issues particularly for problems resulting from climate change.